Clinical Findings and Management of Methanol Induced Toxic Optic Neuropathy: Literature Review - Tristira Urvina; Tristira Rosyida; Erwanda Fredy Purliawan (Malahayati Nursing Journal, 2022)
ABSTRACT Methanol poisoning is a serious problem due to its high mortality and revalence of health sequelae among survivors. Death from methanol poisoning has been reported in 8-36% and permanent vision loss has been observed in 20- 0% of acute trauma survivors. Formic acid that builds up in the optic nerve can disrupt the visual system and cause optic neuropathy. Vision loss is painless and usually occurs in both eyes within one to three days. This Systematic Review based on Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) protocol. This protocol has administered in The International Prospective Register of Systematic Reviews (PROSPERO) database. The literature showed visual acuity and funduscopic examinations of methanol induced optic toxic neuropathy and high-dose steroid, erythropoietin and antioxidant as the therapy. Methanol poisoning is a serious problem due to its high mortality and prevalence of health sequelae among survivors. Pericapillary retinal edema and optic disc edema after blurred vision or "snowfield" vision, visual hallucinations, dense central fibroids, photophobia, peripheral constriction of the visual field, and decreased visual acuity even total blindness as a symptom can be found. Prevention of formic acid formation is the main steps of treatment. Keywords:Methanol, Literature Review, ManagementABSTRACT Methanol poisoning is a serious problem due to its high mortality and revalence of health sequelae among survivors. Death from methanol poisoning has been reported in 8-36% and permanent vision loss has been observed in 20- 0% of acute trauma survivors. Formic acid that builds up in the optic nerve can disrupt the visual system and cause optic neuropathy. Vision loss is painless and usually occurs in both eyes within one to three days. This Systematic Review based on Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) protocol. This protocol has administered in The International Prospective Register of Systematic Reviews (PROSPERO) database. The literature showed visual acuity and funduscopic examinations of methanol induced optic toxic neuropathy and high-dose steroid, erythropoietin and antioxidant as the therapy. Methanol poisoning is a serious problem due to its high mortality and prevalence of health sequelae among survivors. Pericapillary retinal edema and optic disc edema after blurred vision or "snowfield" vision, visual hallucinations, dense central fibroids, photophobia, peripheral constriction of the visual field, and decreased visual acuity even total blindness as a symptom can be found. Prevention of formic acid formation is the main steps of treatment. Keywords: Methanol, Literature Review, Management